2000
DOI: 10.1097/00000478-200002000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Large, Central Acellular Zones Indicating Myoepithelial Tumor Differentiation in High-Grade Invasive Ductal Carcinomas as Markers of Predisposition to Lung and Brain Metastases

Abstract: High-grade invasive ductal carcinomas (IDCs) of the breast with large, central acellular zones on their cut surfaces are usually associated with the myoepithelial immunophenotype of carcinoma cells, which includes the expression of S-100 protein, alpha-smooth muscle actin, and keratin 14. To clarify the clinical significance of these features of IDCs, the authors compared the incidence of the myoepithelial immunophenotype immunohistochemically, patient prognosis, and metastatic sites of the tumor between 20 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
180
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(188 citation statements)
references
References 7 publications
7
180
0
1
Order By: Relevance
“…Such tumours may be worth identifying separately as they probably need a different therapeutic approach. The 'high-grade ductal carcinoma with extensive central scar' (ring carcinoma), may be one of these lesions that is becoming gradually more defined morphologically and clinically, 3,[32][33][34] in spite of the absence of an agreed name. Further analysis of more cases may lead to the identification of other distinct subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Such tumours may be worth identifying separately as they probably need a different therapeutic approach. The 'high-grade ductal carcinoma with extensive central scar' (ring carcinoma), may be one of these lesions that is becoming gradually more defined morphologically and clinically, 3,[32][33][34] in spite of the absence of an agreed name. Further analysis of more cases may lead to the identification of other distinct subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…114 However, when compared with either ERÀ non-basal-like cancers 72 or grade-matched non-basal-like cancers, 42 carcinomas with a basal-like phenotype are not associated with a poorer outcome in some studies, whereas a more adverse prognosis is observed in others. 19,116 The pattern of metastatic spread of tumors with a basal-like phenotype seems to be different from that of non-basal-like cancers: they are reported to less frequently disseminate to axillary nodes and bones 42,117 and to favor a hematogenous spread, 42,[117][118][119] with a peculiar proclivity to develop metastatic deposits in the brain and lungs. 120 It should be noted that patients with triple-negative and basal-like cancers tend to develop adverse events and die due to disease within the first 5-8 years after diagnosis.…”
Section: Clinical Behavior Of Basal-like and Triple-negative Breast Cmentioning
confidence: 99%
“…12 Studies have employed basal/myoepithelial cytokeratins and other markers to identify a subset of ER-and HER2-negative breast carcinomas that are associated with a poor prognosis, further supporting the idea that a basal-like phenotype exists. [13][14][15][16][17][18] The prevalence and poor prognosis of basal-like breast carcinomas have been validated immunohistochemically; in a 564-case tissue microarray, van de Rijn et al 12 demonstrated that 16% of tumors stained positive for cytokeratin 5/6 or cytokeratin 17, and that basal cytokeratin expression was associated with a poor prognosis. Abd El-Rehim evaluated 1944 cases of invasive breast carcinoma and found that approximately 18% of tumors show basal cytokeratin immunoreactivity, and again, these tumors showed a poor prognosis.…”
mentioning
confidence: 99%
“…Abd El-Rehim evaluated 1944 cases of invasive breast carcinoma and found that approximately 18% of tumors show basal cytokeratin immunoreactivity, and again, these tumors showed a poor prognosis. 14 Tsuda et al 17,18 described myoepithelial differentiation in a group of high-grade invasive ductal carcinomas showing a large, central acellular zone. These tumors showed aggressive behavior with increased risk of brain and lung metastasis.…”
mentioning
confidence: 99%